The interplay of poorly soluble drugs in dissolution from amorphous solid dispersions - Marcel Kokott; Jörg Breitkreutz; Raphael Wiedey (Elsevier, 2024)
In recent years, the application of fixed dose combinations of antiretroviral drugs in HIV therapy has been established. Despite numerous therapeutic benefits, this approach poses several challenges for the formulation development especially when poorly soluble drugs are considered. Amorphous solid dispersions (ASD) thereby have gained considerable interest in the pharmaceutical field, however, mainly including binary systems containing only one drug and a polymer. The co-formulation of two amorphous drugs can be accompanied by an immense increase in the complexity of the system as exemplarily reported for ritonavir and lopinavir embedded in a composite polymer matrix of PVPVA. The present study aims to present a new formulation approach to overcome the well-documented interaction during dissolution. Two different polymers, PVPVA and HPMCAS were used to produce ASDs for both drugs individually via hot-melt extrusion. The embedding of lopinavir in the slower dissolving polymer HPMCAS, while using PVPVA for ritonavir was found to significantly improve the overall dissolution performance compared to the individual use of PVPVA as well as to the commercial product Kaletra®. In addition, the use of different grades of HPMCAS demonstrated the possibility to further modify the dissolution profile. For a preliminary biorelevant assessment, the selected formulations were tested in a biphasic dissolution setup.